2010
DOI: 10.1108/13555851011090565
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing tourists' revisit intentions

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 103 publications
11
106
1
5
Order By: Relevance
“…However, perceived quality (B = 0.101; β = 0.095; p = 0.098) and perceived value (B = 0.027; β = 0.023; p = 0.610) are insignificant to tourist satisfaction. These contradict the findings of earlier studies by Chen & Chen (2010) and Quintal & Polczynski (2010). Thus, H1, H4, and H5 are supported while H2 and H3 are rejected.…”
Section: Hypotheses Testingcontrasting
confidence: 91%
See 2 more Smart Citations
“…However, perceived quality (B = 0.101; β = 0.095; p = 0.098) and perceived value (B = 0.027; β = 0.023; p = 0.610) are insignificant to tourist satisfaction. These contradict the findings of earlier studies by Chen & Chen (2010) and Quintal & Polczynski (2010). Thus, H1, H4, and H5 are supported while H2 and H3 are rejected.…”
Section: Hypotheses Testingcontrasting
confidence: 91%
“…Past studies have also suggested that perceptions of service quality and value affect satisfaction, and satisfaction then affects loyalty and post-behaviors (de Rojas & Camarero, 2008;Chen, 2008;Chen & Tsai, 2007;Choi & Chu, 2001). A positive relationship between the two constructs has also been confirmed in prior investigations (Quintal & Polczynski, 2010;Ruiz et al, 2009;de Rojas & Camarero, 2008;Um et al, 2006;Howat & Murray, 2002;Baker & Crompton, 2000). Goodrich (1978) assert that, "The more favorable the perception of a given vacation destination, the more preferred that destination will tend to be" (p. 11).…”
Section: Tourists' Perceived Quality In Relation To Tourist Satisfactionmentioning
confidence: 52%
See 1 more Smart Citation
“…Whisman and Hollenhorst [41] claimed that satisfaction can be measured through the quality of offered services, ecological conditions, natural landscapes and secure facilities available at destinations. Once these conditions are satisfied, tourists tend to have a positive attitude and perception of the leisure episode and quality of the tourism destination as there is a positive relationship between the perceived quality of a destination and the tourist satisfaction [31,[42][43][44].…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Empirical evidence showed that online reviews have significant influence on destination image (e.g., Govers & Go, 2004;Mridula, 2009), destination choice (Jalilvand & Samiei, 2012b) and revisit intention (e.g., Kim et al, 2012;Quintal & Polczynski, 2010) of tourists.…”
Section: Introductionmentioning
confidence: 99%